EFFECT OF POST-LOGGING SILVICULTURAL TREATMENT ON GROWTH RATES OF RESIDUAL STAND IN A TROPICAL FOREST - Krisnawati, Haruni; Wahjono, Djoko (Indonesian Journal of Forestry Research, 2010)
Post-logging silvicultural treatments are generally performed to improve yields of the remaining tree species by increasing their growth rate. In this study the effects of silvicultural treatment on the growth rates of commercial (dipterocarps and non-dipterocarps) as well as non- commercial tree species in a tropical forest in West Kalimantan were examined and were compared to a control treatment. Silvicultural treatment applied was liberation of future crop trees from lianas and neighbouring competing trees. Treatments were applied to six plots of 80 m x 80 m each. The plots comprised 64 quadrats of 10 m x 10 m to allow better control of measurements. The treatment and control plots were established 6 years after logging. Effects were measured 2,4 and 7 years after treatment application. In all obser vation periods, the growth rates increased with silvicultural treatment. Overall, commercial dipterocarps, commercial non-dipterocarps and non-commercial tree species groups differed in response to silvicultural treatment. The growth rates of commercial tree species in plots that received silvicultural treatment were 62â97% higher than in the control plots. For non-commercial tree species, the increase of growth rates was 20â58%, compared to the control plots. These results indicate that the application of silvicultural treatments after logging could help improve the growth of the residual stands. These provide quantitative information that silvicultural treatments in logged-over forest should be considered as a viable management option and may guide the choice of cutting cycle.